(untitled) (Herald of Journalism, 2021)
The socio-psychological adaptation of migrants is a complex of multi-level communications. An important role in this process is played by the media, social networks and instant messengers. In this context, the authors of the study focused on the constructive capabilities of media in the sphere of influence on the level of communicative competencies of migrants, their social adaptation and inclusion in the national Kazakhstani discourse. The authors also proposed their own typology of models of information support for the topic of Kandas in Kazakhstan: synchronous (event-driven); asynchronous (random); conveyor (streaming) and model-concept by and large. The purpose of this article is to present the main indicators of information support for the socio-psychological adaptation of Kandas in Kazakhstan, to identify the determinants of perception of a new reality, to overcome the stress of acculturation. The main idea of ​research is the proposed algorithms for understanding Kandas queries, the formulation of negative and positive discrepancies with basic expectations. The methodology of polling Kazakhstanis and Kandas made it possible to identify a number of conceptual problems, including the average level of competence of indigenous Kazakhstanis on migration and Kandas, a satisfactory response of Kandas to government programs and a low level of trust in some forms of communication within Kazakhstani society. The main results of the study made it possible to form a list of destabilizing factors for the successful social adaptation of Kandas and to determine the desired concept of coverage of this topic in the media. From a practical and value point of view, this material can be extrapolated into a conceptual model of information work with the topic of migration and socio-psychological adaptation of Kandas in Kazakhstan. Key words: Kandas, government programs, mass media, immigrants, socio-psychological adaptation.